2021
DOI: 10.1021/acs.jafc.1c04378
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Stress-Induced β-Ocimene Biosynthesis in Tea (Camellia sinensis) Leaves during Oolong Tea Processing

Abstract: As the major contributors to the floral odors of tea products, terpenoid volatiles play critical roles in the defense response of plants to multiple stresses. Until now, only a few TPS genes in tea plants (Camellia sinensis) have been functionally validated. In this study, by comparative studies conducted at gene, protein, and metabolite levels during oolong tea processing, we isolated an ocimene synthase gene, CsOCS, which displays a low similarity to previously characterized tea ocimene synthases. Further pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
(106 reference statements)
1
20
0
Order By: Relevance
“…A tea CsOCS (TEA014989.1) and snapdragon ( ama0a23 ) encodes (E)-β-ocimene synthase; both catalyze GPP to produce predominantly (E)-β-ocimene and a small amount of (Z)-β-ocimene. 40 , 45 In this study, both (E)-β-ocimene and (Z)-β-ocimene were detected, and both showed biphasic peaks at 4 and 8 h spreading ( Figures 1 and 5 b). From 0 to 6 h, the ratio of (E)-β-ocimene to (Z)-β-ocimene was around 2 and increased to 5 at 8 h of spreading ( Figure 5 c).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…A tea CsOCS (TEA014989.1) and snapdragon ( ama0a23 ) encodes (E)-β-ocimene synthase; both catalyze GPP to produce predominantly (E)-β-ocimene and a small amount of (Z)-β-ocimene. 40 , 45 In this study, both (E)-β-ocimene and (Z)-β-ocimene were detected, and both showed biphasic peaks at 4 and 8 h spreading ( Figures 1 and 5 b). From 0 to 6 h, the ratio of (E)-β-ocimene to (Z)-β-ocimene was around 2 and increased to 5 at 8 h of spreading ( Figure 5 c).…”
Section: Resultssupporting
confidence: 52%
“…Thus, additional FPP should be generated de novo to drive the increase. Meanwhile, other factors should be taken into account which could support this hypothesis: (1) the targeted metabolic profiling in this study could miss some unidentified sesquiterpenes which are involved in the sesquiterpene interconversion; (2) sesquiterpene glycosides and esters have been found from other plant species; they could also be present in fresh tea leaves. During 4 to 10 h spreading, these compounds could be released by glycosidases and contribute to the total sesquiterpene increase.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In tea leaves, α-Farnesene and Ocimene have been found to be synthesized de novo in tea leaves treated with jasmonic acid and mechanical damage (JAMD) and pass between tea plants to initiate volatile defense mechanisms of undamaged tea plants [ 29 ]. In another report, CsOCS was mentioned as a key synthase to promote the de novo synthesis of β-ocimene in oolong tea processing, which is one of the important defense signals of the tea plant against adversity [ 30 ]. These reports suggested that although some of the aforementioned terpene substances (such as α-Farnesene, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, bifunction and multifunction is another common phenomenon in TPS, meaning that two or more products can be catalyzed by a single TPS (Liu et al, 2021; Zerbe et al, 2012). Deep analysis and discovery of TPS function associated with specific terpenoid is a key topic of investigation in plants (Chen et al, 2021). Although it is still unclear how terpenoids are synthesized in P .…”
Section: Discussionmentioning
confidence: 99%